2005
DOI: 10.1073/pnas.0507263102
|View full text |Cite
|
Sign up to set email alerts
|

Breath sulfides and pulmonary function in cystic fibrosis

Abstract: We have determined the concentrations of carbonyl sulfide (OCS), dimethylsulfide, and carbon disulfide (CS 2) in the breath of a group of cystic fibrosis (CF) patients and one of healthy controls. At the detection sensitivity in these experiments, room air always contained measurable quantities of these three gases. For each subject the inhaled room concentrations were subtracted from the timecoincident concentrations in exhaled breath air. The most significant differences between the CF and control cohorts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 30 publications
(23 reference statements)
3
68
1
Order By: Relevance
“…In the euglycemic group, methyl nitrate concentrations averaged 11 Ϯ 3 pptv at the beginning of the study; after euglycemia was maintained for 2 h, methyl nitrate concentrations were not significantly different (8 Ϯ 1 pptv; P ϭ 0.32). These data are consistent with our previous findings of the measurable amount of 5 pptv of methyl nitrate in the breath of healthy subjects (⌬: room, 5 Ϯ 2 pptv; breath, 10 Ϯ 2 pptv) (4,5). Conversely, in the hyperglycemic group, initial methyl nitrate concentrations were significantly greater (27 Ϯ 6 pptv) and decreased significantly after hyperglycemia was corrected (15 Ϯ 2 pptv; P ϭ 0.01).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In the euglycemic group, methyl nitrate concentrations averaged 11 Ϯ 3 pptv at the beginning of the study; after euglycemia was maintained for 2 h, methyl nitrate concentrations were not significantly different (8 Ϯ 1 pptv; P ϭ 0.32). These data are consistent with our previous findings of the measurable amount of 5 pptv of methyl nitrate in the breath of healthy subjects (⌬: room, 5 Ϯ 2 pptv; breath, 10 Ϯ 2 pptv) (4,5). Conversely, in the hyperglycemic group, initial methyl nitrate concentrations were significantly greater (27 Ϯ 6 pptv) and decreased significantly after hyperglycemia was corrected (15 Ϯ 2 pptv; P ϭ 0.01).…”
supporting
confidence: 82%
“…The extreme versatility of exhaled gas analysis (combining simultaneous measurements of 100 or more exhaled gases in each breath with easy, noninvasive, and painless collection methods) therefore appears especially suitable for the definition and monitoring of the time course of evolving, complex metabolic conditions, including, among others, inflammation, dyslipidemia, and diabetes. In recent years, our laboratory has concentrated on this approach for the use of exhaled VOC analysis in pathological conditions (4,5). In this study, we describe the potential applications of VOC analysis to the monitoring of hyperglycemia in type 1 diabetes mellitus (T1DM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Average values for acetone and dimethyl sulfide were comparable to that observed in healthy adults (displayed in Table 1) whilst average methanol and isoprene values in the study subjects were generally lower than that observed in the group of healthy adults (consistent with a previous study on children's breath (Taucher et al, 1997)). Previous reports have linked dimethyl sulfide and isoprene to cystic fibrosis and respiratory exacerbation (Barker et al, 2006;Kamboures et al 2005;McGrath et al, 2000). However, the present results indicate no significant difference between dimethyl sulfide and isoprene in the cystic fibrosis ( (Wang et al, 2006;Enderby et al, 2009).…”
Section: Direct Ptr-tof-ms Applied To Fingerprinting Breathcontrasting
confidence: 56%
“…It is an excellent experimental tool that can reveal the behavior of CF microbes in an environment more similar to the CF lung. For example, DMDS was detected in headspace gas from WinCF capillary tubes and breath gas samples from CF patients (Kamboures et al, 2005;Barker et al, 2006). DMDS is a major by-product of methionine degradation (Segal and Starkey, 1968), and methionine is a major component of the mucin glycopeptide.…”
Section: Sources Of the Fermentative Responsementioning
confidence: 99%